Population dynamics of pronghorn spiny lobster (Panulirus penicillatus) in Palabuhanratu Bay, Sukabumi, West Java - Mennofatria Boer; Rudi Alek Wahyudin; Yusli Wardiatno; Achmad Farajallah; Agus Alim Hakim (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Pronghorn spiny lobster (Panulirus penicillatus) is one of the dominant lobsters and has high economic value. The fishing activities are conducted continuously and put aside the preservation of these resources. This study purposed to analyze the population dynamics of pronghorn spiny lobster (Panulirus penicillatus) in Pelabuhanratu Bay, Sukabumi, West Java. The data were collected from January until December 2016 with samples from local fisherman. Lobsters were measured carapace length and total weight. Data analysis included the relationship between length and weight, growth parameters, recruitment patterns, mortality, exploitation rate, length at first maturity or incubating eggs (Lr), and length for first capture (Lc). Panulirus penicillatus from the Palabuhanratu Bay has growth pattern of a negative allometric in both males and females. The asymptotic carapace length (CL∞) of males is higher than females while the growth coefficient (K) of males is lower than females. The peak recruitment for males is expected to be in April and July, while for females in May and August. The total mortality rate of males is higher than the natural mortality rate and vice versa for females. The male lobsters have occurred overexploitation, while females have not occurred overexploitation. The female lobsters have an Lr <Lc value which indicates that the female lobsters are caught after incubating the eggs.